Spinal cord stimulation using time-dynamic pulses achieves longer reversal of allodynia compared to tonic pulses in a rat model of neuropathic pain - Zhu, Changfang; Jeong, Ki-Soo; Edhi, Muhammad; Rogness, Victoria; Saab, Carl Y.; Esteller, Rosana (Frontiers in Pain Research, 2025)
BackgroundSpinal cord stimulation (SCS) utilizing time-dynamic pulses (TDPs) is an emergent field of neuromodulation that continuously and automatically modulates pulse parameters. We previously demonstrated that TDPs delivered for 60 min at paresthesia-free or minimal paresthesia amplitudes significantly reversed allodynia in a rat model of neuropathic pain. Because the anti-allodynic effect was observed to persist post-stimulation, we hypothesized that the anti-nociceptive effects of TDPs may persist longer than those of tonic stimulation.MethodsWe extended SCS stimulation period up to 90 min and investigated the temporal dynamics of SCS-induced analgesia through PWT analysis of the aggregated data from both cohorts.ResultsBoth TDPs and tonic stimulation reversed paw withdrawal thresholds (PWT) to near pre-neuropathic levels within 30 min. Most TDPs exhibited significantly slower ramp-up slope (analgesia ‘wash-in' rates) as compared to tonic stimulation. All TDPs showed slower wind-down slopes (analgesia ‘wash-out’ rates) compared to tonic, with pulse width modulation reaching significance. Extending SCS from 60 to 90 min revealed that all TDPs maintained analgesic efficacy longer than tonic stimulation, which showed significant decrease at both 75 and 90 min.DiscussionAlthough TDPs and tonic stimulation comparably mitigated allodynia, TDPs exhibited slower rate of wash-out, suggesting longer-lasting analgesic effects and potentially different mechanisms of action.